2010
DOI: 10.3945/ajcn.2010.29353
|View full text |Cite
|
Sign up to set email alerts
|

α1-Acid glycoprotein, hepcidin, C-reactive protein, and serum ferritin are correlated in anemic schoolchildren with Schistosoma haematobium

Abstract: Correlations between AGP, CRP, urinary hepcidin, and SF were statistically significant. CRP values explained SF's variance better than did the other markers of inflammation studied. We therefore recommend the measurement of both AGP and CRP in population surveys that include an assessment of iron deficiency in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 9 publications
3
25
2
Order By: Relevance
“…The WHO and the United States CDC experts also stress that inflammatory indicators need to be detected when detecting indexes of iron nutritional status [16]. Studies have shown that AGP and CRP are significantly correlated with SF, and it is suggested to detect AGP and CRP simultaneously when assessing the nutritional status of iron [17]. Therefore, we grouped the subjects according to AGP and CRP to examine the effect of inflammation on the diagnostic accuracy of CHr.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO and the United States CDC experts also stress that inflammatory indicators need to be detected when detecting indexes of iron nutritional status [16]. Studies have shown that AGP and CRP are significantly correlated with SF, and it is suggested to detect AGP and CRP simultaneously when assessing the nutritional status of iron [17]. Therefore, we grouped the subjects according to AGP and CRP to examine the effect of inflammation on the diagnostic accuracy of CHr.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only CRP currently recommended by WHO as an independent indicator of the acute phase response (57) was used. It is shown to explain serum ferritin variance better than other markers of inflammation (58). We corrected the PF values for inflammation using correction factors that are better than adjusting the cutoff value upwards or excluding those with inflammation (35,57).…”
Section: Discussionmentioning
confidence: 99%
“…The definitions we used were anaemia: haemoglobin concentration <110 g/L [41]; iron deficiency: plasma ferritin concentration <12 μg/L [42]; Plasmodium infection: presence of parasites and gametocytes of any Plasmodium species [43]; inflammation: plasma CRP concentration >5 mg/L [44] or plasma α 1 -acid glycoprotein concentration >1.0 g/L [45], respectively. Group adherence was defined as the proportion of children who consumed ≥24 home fortification doses, corresponding to ≥80% of the 30 scheduled doses [46], with exclusion of children who were lost to follow-up because they moved out of the study area.…”
Section: Methodsmentioning
confidence: 99%